Drag area, frontal area and drag coefficient in cross-country skiing techniques - Ainegren, M.; Jonsson, P. (Proceedings, 2018)
The aim of this study was to investigate the air drag, frontal area and coefficient of drag of cross-country skiing classical and free style techniques. One highly skilled cross-country skier performed skiing-like classical and free style techniques on a force plate in a wind tunnel. The skier was also photographed from the front in order to analyze the projected frontal area, which was determined from digital images using Matlab. From the results of the air drag and the frontal area measurements, the drag coefficient was also calculated. The results can be used by researchers to calculate the theoretical effect of air drag on cross-country skiing performance.